An efficient modified grey wolf optimizer with Lévy flight for optimization tasks - Heidari, Ali Asghar; Pahlavani, Parham (Applied soft computing, 2017)
[Display omitted] . •A novel modified GWO with levy flight is developed, called LGWO.•Several benchmarks were employed and statistical comparisons were performed to investigate the efficiency of the LGWO.•Experiment results revealed that levy flight can significantly improve the search.•LGWO outperforms GWO and several heuristic algorithms in tackling mathematical and real-world optimization tasks. The grey wolf optimizer (GWO) is a new efficient population-based optimizer. The GWO algorithm can reveal an efficient performance compared to other well-established optimizers. However, because of the insufficient diversity of wolves in some cases, a problem of concern is that the GWO can still be prone to stagnation at local optima. In this article, an improved modified GWO algorithm is proposed for solving either global or real-world optimization problems. In order to boost the efficacy of GWO, Lévy flight (LF) and greedy selection strategies are integrated with the modified hunting phases. LF is a class of scale-free walks with randomly-oriented steps according to the Lévy distribution. In order to investigate the effectiveness of the modified Lévy-embedded GWO (LGWO), it was compared with several state-of-the-art optimizers on 29 unconstrained test beds. Furthermore, 30 artificial and 14 real-world problems from CEC2014 and CEC2011 were employed to evaluate the LGWO algorithm. Also, statistical tests were employed to investigate the significance of the results. Experimental results and statistical tests demonstrate that the performance of LGWO is significantly better than GWO and other analyzed optimizers.